2014
DOI: 10.1016/j.tox.2014.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Use of OpdA, an organophosphorus (OP) hydrolase, prevents lethality in an African green monkey model of acute OP poisoning

Abstract: Organophosphorus (OP) pesticides are a diverse class of acetylcholinesterase (AChE) inhibitors that are responsible for tremendous morbidity and mortality worldwide, killing approximately 300,000 people annually. Enzymatic hydrolysis of OPs is a potential therapy for acute poisoning. OpdA, an OP hydrolase isolated from Agrobacterium radiobacter, has been shown to decrease lethality in rodent models of OP poisoning. This study investigated the effects of OpdA on AChE activity, plasma concentrations of OP, and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…Plasma AChE activity was assayed to determine the chronic poisoning effects of isocarbophos. In Table S1, plasma AChE activities were identical in each group during the whole experiments (the 4th–16th week), indicating that the chronic administration of isocarbophos has no inhibitory effects on the plasma AChE activity, which is different to acute organophosphor poisoning as it decreases plasma AChE activity 18.…”
Section: Resultsmentioning
confidence: 95%
“…Plasma AChE activity was assayed to determine the chronic poisoning effects of isocarbophos. In Table S1, plasma AChE activities were identical in each group during the whole experiments (the 4th–16th week), indicating that the chronic administration of isocarbophos has no inhibitory effects on the plasma AChE activity, which is different to acute organophosphor poisoning as it decreases plasma AChE activity 18.…”
Section: Resultsmentioning
confidence: 95%
“…Of special importance are the results reported by Jackson et al [20], wherein the catalytic scavenger, a wt OpdA, was demonstrated for the first time to confer full and sign-free protection in a non-human primate. Thus, as low as 1.2 mg/kg enzyme alone conferred remarkable protection against 3×LD 50 (75 mg/kg) of orally administered dichlorvos.…”
Section: Resultsmentioning
confidence: 99%
“…Protection experiments in vivo confirmed the capacity of catalytic scavengers such as wt parathion hydrolase from Pseudomonas sp. [13,14], mammalian PONs [15,16], PTEs from Brevudimonas diminuta [17], and OpdA from Agrobacterium radiobacter [18,19,20], to prevent lethality at less than 1mg/kg of catalytic enzyme, and even to confer sign-free protection in several cases in animal intoxication models. It should be pointed out that although evolved variants of bacterial OP hydrolases display high catalytic activity against a variety of nerve agents [8-12], their wt forms as well, as well as mammalian wt OP hydrolases, are considered to be poor antidotes for treatment of nerve agent intoxication [6].…”
Section: Introductionmentioning
confidence: 99%
“…The addition of OpdA to usual clinical treatment might improve the effectiveness of treatment for OP pesticide poisoning, in particular allowing oximes to work in mega-dose suicides [24]. It prevents death in rats when given immediately after dosing with highly toxic dichlorvos, parathion or methyl parathion OP insecticides, improving the effectiveness of pralidoxime [25], and prevents acute toxicity after oral dichlorvos poisoning in non-human primates [26,27]. However, before development can start, additional studies are required.…”
Section: Introductionmentioning
confidence: 99%